ANALISIS PENDAPATAN USAHATANI CABAI MERAH DI DAERAH NON SENTRA PRODUKSI DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR PROVINSI RIAU - Ilma Satriana Dewi; Sri Ayu Kurniati; Jeffry Andrian (UIR Press, 2023)
Red chili is one of the horticultural crops that is suitable for cultivation in tropical climates areas. Even though red chilies have started to be widely cultivated, the success rate in cultivating this commodity is still low, especially in areas that are not become red chili production centers. One of the causing factors of the experience of farmers who are still low, there is no government support for farmers who cultivate red chilies, and it takes quite a lot of capital, especially in maintenance because red chili plants are quite vulnerable to pests and diseases. Based on this explanation, this research aimed to analyze red chili cultivation technology and analyzed red chili farming income. The research method was carried out by survey in Bangkinang Kota sub-district that is not a chili production center. The number of respondents taken by census as many as 30 people. The results showed that the red chili cultivation technology carried out in the research area was in general almost in accordance with the recommendation from AIAT. Even so, there were slight differences in the fertilization process, especially in the amount of NPK fertilizer used which was more than the recommended dose. In addition, the frequency of the number of harvests was less (10 times) than the conditions that should be (12-20 times). Furthermore, the total production costs incurred for cultivating red chili plants amounted to IDR 25,299,160. The average amount of production was 3,000 kg with the selling price in effect at the time of the research being IDR 26,000/kg. The average total income was IDR 78,000,000 and the profit from farming was IDR 52,700,840. The efficiency of red chili farming was 3.08, means that this business was profitable and feasible to run